Direct quantification of protein glycan phosphorylation. (September 2017) - Ketcham, Stephanie A.; Ashraf, Muhammad; Madhavarao, Chikkathur N.
Phosphorylation is an important post-translational modification (PTM) of proteins and a critical quality attribute for protein therapeutics, especially if it is required for protein function or sub-cellular targeting. Most current methods to quantify phosphorylation are time-consuming, indirect, or require specific instrumentation and technical skills. Here, we report the adaptation of a phosphate-specific binding dye and common laboratory instruments for quantification of relative amounts of phosphorylated glycans as well as phosphorylation of amino acid residues on the backbones of proteins. Our results show that quantification of phosphorylation using the new method agrees with published data on the number of phosphorylated glycosylation sites for two lysosomal enzymes: β-glucuronidase (GUS) and cathepsin D.